A Working Memory Account of the Interaction between Numbers and Spatial Attention. Issue 8 (August 2014) - van Dijck, Jean-Philippe; Abrahamse, Elger L.; Acar, Freya; Ketels, Boris; Fias, Wim
Rather than reflecting the long-term memory construct of a mental number line, it has been proposed that the relation between numbers and space is of a more temporary nature and constructed in working memory during task execution. In three experiments we further explored the viability of this working memory account. Participants performed a speeded dot detection task with dots appearing left or right, while maintaining digits or letters in working memory. Just before presentation of the dot, these digits or letters were used as central cues. These experiments show that the "attentional SNARC-effect" (where SNARC is the spatial–numerical association of response codes) is not observed when only the lastly perceived number cue—and no serially ordered sequence of cues—is maintained in working memory (Experiment 1). It is only when multiple items (numbers in Experiment 2; letters in Experiment 3) are stored in working memory in a serially organized way that the attentional cueing effect is observed as a function of serial working memory position. These observations suggest that the "attentional SNARC-effect" is strongly working memory based. Implications for theories on the mental representation of numbers are discussed.